Effect of Proteolytic Modification on Texture and Mastication of Heat‐Treated Egg White Gels. Issue 1 (6th May 2016) - Funaki, Junko; Minami, Michiko; Abe, Sachie; Ueda, Reiko; Eto, Wakako; Kugino, Kenji; Kugino, Mutsuko; Abe, Keiko; Toko, Kiyoshi; Asakura, Tomiko
Abstract: Raw egg white undergoes sol–gel transition by heat treatment, which changes it to an elastic gel. Here, protease treatment to render a new texture to heated egg white gel was applied. Protease‐treated gels exhibited ductile flow without obvious rupture points. Transmission electron microscopy analysis showed that in protease‐treated gels, protein aggregates were distributed more homogeneously compared with that observed in the untreated control, probably because ovalbumin was digested into small peptides as revealed by SDS‐PAGE. The properties of the gel were evaluated by sensory tests and by measuring the movement of the masseter muscle, using surface electromyography. Results showed that maximum bite force and mastication duration were decreased for the protease‐treated gels, which were evaluated as being softer, smoother, less elastic and better textured. Overall, our results indicate that protease‐treated egg white gel has superior qualities and is easier to swallow than the untreated gel. Practical Applications: In the food industry, the use of egg white is limited compared with that of egg yolk and whole eggs. In this study, we performed protease treatment to generate a new food material with smoother and softer texture compared with heat treated egg white. Our findings may expand the consumption of egg white, which can be consumed by people with mastication and swallowing disorders, and reduce the waste of egg white as a surplus product.